SMEs and their bank choices: trust-related factors or economic calculations?. Issue 8 (29th June 2020) - Jackowicz, Krzysztof; Kozłowski, Łukasz; Strucinski, Adrian
Abstract : Purpose: The authors investigate the factors affecting the decision of small and medium-sized enterprises (SMEs) to do business with either small local banks or large commercial banks. Design/methodology/approach: We combine various data sources on Polish SMEs, including their financial statements, county-level data on SMEs' local environment, information about bank branch locations, as well as a new survey on the specificity of bank–firm relationships. We employ the logit and Tobit models. Findings: SMEs' bank choices and the length of a bank–firm relationship are more strongly associated with trust-related factors, rather than transactional ones. SME managers motivated by trust-related factors are more likely to choose local lenders and maintain long-term relationships with them. However, as firms grow and mature, SME managers lean toward banks adopting transaction-oriented policies. Research limitations/implications: We could have drawn a more detailed picture of the bank selection process had we been able to compare the traits of a firm's current and previous banks. Practical implications: The study shows that the features of a bank's offer, including product prices, have limited potential in shaping long-term relationships between banks and SMEs. Originality/value: The topic of bank selection by SMEs has not been thoroughly investigated in the case of Central European countries. We address this gap by comparing two types of potential drivers of bank selection: trust-related factors and a set of purely economic (transactional) motives.